EMOTIONAL INTELLIGENCE AND AGGRESSIVE BEHAVIOR OF VOCATIONAL STUDENT - Herawati, Anna Ayu; DHARMAYANA, I WAYAN; SHOLIHAH, AFIFATUS (TRIADIK, 2017)
Abstract: The objective of this research is to: (1) to described of emotional intelligence at SMKN 2 Bengkulu, (2) to described aggressive behavior at SMKN 2 Bengkulu, (3) to described correlations between emotional intelligence with aggressive behavior students of ten grade TM (Teknik Mesin) at SMKN 2 Bengkulu. This research was conducted at SMKN 2 Bengkulu with sample =50 students from total population (110) of students ten grade TM SMKN 2 Bengkulu . The method that used in this research was quantitative correlations design, analytical techniques that used are correlations product moment from Karl Pearson. The result of this research were found a strong negative correlations (with score rxy = -0,709) between emotional intelligence with aggressive behavior of adolescent student of ten grade TM (Teknik Mesin) at SMKN 2 Bengkulu.Keywords: emotional intelligence, aggressive behavior